solve the equation using the quadratic formula.

2x^2 + 6x + 2 = 0

Where a = 2 b = 6 c = 2

Now the quadratic formula is

( - b ± √b^2 - 4ac ) / 2a

Now putting the values , we get

= ( -6 ± √6^2 - 4(2)(2) ) / 2(2)

= ( -6 ± √36 - 16 ) / 4

= ( -6 ± √20 ) / 4

= ( -6 ± √4*5 ) / 4

= ( -6 ± 2√5 ) / 4

Now taking 2 common, we get

= 2( -3 ± √5 ) / 4

= ( -3 ± √5 ) / 2

Hence the roots are ( -3 ± √5 ) / 2

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up